Strategy for Improving Micro, Small and Medium Enterprises (MSMEs) Through Innovation in Medan, North Sumatra - Simanjuntak, Gracesiela Yosephine; Ginting, Mitha C.; Sagala, Farida; Sagala, Lamria; Elisabeth, Duma Megaria; Silitonga, Ivo Maelina; Nadapdap, Kristanty M.N.; Goh, Thomas Sumarsan; Simanjuntak, Faido M. P.; Sembiring, Yosephine N. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine MSME product innovation and highlight the obstacles they face. The obstacles faced by small and medium businesses are usually not focusing on development, product innovation still relying on old products and lack of capital, and product development strategies are still lacking. Product innovation within a company is very important for company sustainability. Service activities will be carried out using descriptive research methods using a qualitative approach. Data sources were obtained through field observations and interviews with informants. The participation and enthusiasm of MSME players in this activity was very good and they actively participated in implementing the training. Economic actors must be wise in looking for new innovations so that consumers are more satisfied when buying these products. The community's economy is supported by the presence of MSMEs, so that most of the community's income comes from MSMEs. However, because there are still many MSMEs that do not have access to financial institutions, loan capital is currently limited.